Gene Therapy for Neuropathic Pain through siRNA-IRF5 Gene Delivery with Homing Peptides to Microglia - Tomoya Terashima; Nobuhiro Ogawa; Yuki Nakae; Toshiyuki Sato; Miwako Katagi; Junko Okano; Hiroshi Maegawa; Hideto Kojima (Elsevier, 2018)
Astrocyte- and microglia-targeting peptides were identified and isolated using phage display technology. A series of procedures, including three cycles of both in vivo and in vitro biopanning, was performed separately in astrocytes and in M1 or M2 microglia, yielding 50-58 phage plaques in each cell type. Analyses of the sequences of this collection identified one candidate homing peptide targeting astrocytes (AS1[C-LNSSQPS-C]) and two candidate homing peptides targeting microglia (MG1[C-HHSSSAR-C] and MG2[C-NTGSPYE-C]). To determine peptide specificity for the target cell in vitro, each peptide was synthesized and introduced into the primary cultures of astrocytes or microglia. Those peptides could bind to the target cells and be selectively taken up by the corresponding cell, namely, astrocytes, M1 microglia, or M2 microglia. To confirm cell-specific gene delivery to M1 microglia, the complexes between peptide MG1 and siRNA-interferon regulatory factor 5 were prepared and intrathecally injected into a mouse model of neuropathic pain. The complexes successfully suppressed hyperalgesia with high efficiency in this neuropathic pain model. Here, we describe a novel gene therapy for the treatment neuropathic pain, which has a high potential to be of clinical relevance. This strategy will ensure the targeted delivery of therapeutic genes while minimizing side effects to non-target tissues or cells.